Reasoning about Recursive Probabilistic Programs - Olmedo, Federico; Kaminski, Benjamin Lucien; Katoen, Joost-Pieter; Matheja, Christoph (Proceedings of the 31st Annual ACM/IEEE Symposium on Logic in Computer Science, 2016)
This paper presents a wp--style calculus for obtaining expectations on the outcomes of (mutually) recursive probabilistic programs. We provide several proof rules to derive one-- and two--sided bounds for such expectations, and show the soundness of our wp--calculus with respect to a probabilistic pushdown automaton semantics. We also give a wp--style calculus for obtaining bounds on the expected runtime of recursive programs that can be used to determine the (possibly infinite) time until termination of such programs.